2019
DOI: 10.26452/ijrps.v10i3.1469
|View full text |Cite
|
Sign up to set email alerts
|

A review on the neuroprotective effect of Nelumbo nucifera seed pod

Abstract: Receptaculum Nelumbinis, the dried seed pod of Nelumbo nucifera, exhibited good efficacy for improving learning and memory abilities. Earlier, studies revealed that Receptaculum Nelumbinis can exert therapeutic effects in diverse disorders like heart failure, neoplasm via anti-oxidative, anti-inflammatory and anti-proliferative activities. In the central nervous system (CNS), Receptaculum Nelumbinis (RN) also has beneficial effects on various disorders, such as Alzheimer's disease (AD), depression, Parkinson's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…It has been demonstrated that some common food flavonoids can function as effective stabilisers of oil-in-water emulsions by adhering as water-insoluble particles to the oil droplets' surfaces, i.e., Pickering emulsions. A yellow colour formed after mixing 2 ml of orange peel extract with 1 ml of 2N sodium hydroxide suggests the presence of flavonoids [11].…”
Section: Test For Flavonoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that some common food flavonoids can function as effective stabilisers of oil-in-water emulsions by adhering as water-insoluble particles to the oil droplets' surfaces, i.e., Pickering emulsions. A yellow colour formed after mixing 2 ml of orange peel extract with 1 ml of 2N sodium hydroxide suggests the presence of flavonoids [11].…”
Section: Test For Flavonoidsmentioning
confidence: 99%
“…Three to four drops of ferric chloride at 1% were then added. After that, a blue-black or brownish-green color was observed [11]. 4.3.5.…”
Section: Test Formentioning
confidence: 99%
“…A significant difference was considered b/w group when p<0.05. All analyses were done with GraphPad Prism 8.0.2 software [9,10,11,24] .…”
Section: 10statistical Analysismentioning
confidence: 99%
“…12 The extract of N. nucifera also reported activity against neurodegenerative diseases. 13 Various benzyl tetrahydroisoquinolne (BTIQ) and aporphine (i.e., nuciferine and nornuciferine), alkaloids found in lotus flower and leaves 14 displayed many neuropharmacological activities. The alkaloid fraction of lotus leaveshave also showed prominent anxiolytic, sedative and hypnotic potential by binding with GABA receptor and stimulating the monoaminergic receptor system.…”
Section: Introductionmentioning
confidence: 99%